The Effects of Thymoquinone of Black Seed Plant on Sperm Parameters, Hormones, and Oxidative Stress in Mice Poisoned by Chlorpyrifos - Nozad, Azita; Hanachi, Parichehr; Mohebali, Shahrdad (Archives of Advances in Biosciences, 2024)
Introduction: The Nigella sativa plant, commonly known as black seed, contains a significant compound known as thymoquinone, which exhibits remarkable therapeutic properties. This study aimed to assess the potential therapeutic effects of thymoquinone on the adverse effects of chlorpyrifos toxicity, considering the importance of reproductive capacity and the detrimental impacts of agricultural toxins. Materials and Methods: Various parameters were assessed in 36 NRMI male mice including testosterone and luteinizing hormone (LH) hormone secretion, sperm count and motility, as well as an antioxidant activity measured by TAC (Total Antioxidant Capacity), MDA (malondialdehyde), and SOD (Superoxide Dismutase). Both thymoquinone and chlorpyrifos were injected intraperitoneally for 14 days. Results: In tests related to sperms, chlorpyrifos caused a severe decrease in sperm motility and number (p<0.001). The administration of chlorpyrifos poison caused a significant decrease in the secretion of testosterone and LH hormones (p<0.05). However, these adverse effects were partially reduced by thymoquinone injection together with chlorpyrifos, especially at a dose of 10 mg/kg. Based on the results of TAC, MDA and SOD antioxidant assays, chlorpyrifos poison caused a significant decrease in antioxidant capacity (p<0.001). In contrast, injection of thymoquinone with a dose of 10 mg/kg caused a significant improvement in the increase of antioxidant capacity in the testicular tissue (p<0.05). Conclusion: According to the observed results and therapeutic effects, a dosage of 10 mg/kg thymoquinone is recommended for reduce oxidative stress-induced injury and toxin-mediated toxicity and enhance sexual traits. Overall, thymoquinone shows potential as a therapeutic agent, and further research could explore its applications in mitigating oxidative stress-related damage and improving sexual function.